PERFORMANCE ANALYSIS OF IRRIGATION AREA IN PEMALI BREBES - Muhamad Salman Salahuddin; Saihul Anwar; Heri Mulyono (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2020)
Irrigation Area Pemali comprised in the district of Banjarharjo Brebes Center Java, the located Approximately less than 50 km from Cirebon and 40 km from Bradford Center Java, and exist some villages such as, Cikakak, Coral Maja, Tiwulandu Village in East and Tonjong, shovel , Gandol in West.Irrigation Area Pemali duct have the name is the Regional Master Irrigation Pemali or named DI Jangkelok Hilir. At first, the water Able to dilute more less 6677ha but in this time only more less 6349ha, the trouble is the diversion of the use of land. This Pemali irrigation area was built in the years 1901 - 1904. The irrigation areas of irrigation area Pemali supply six kemantren such as Kemantren Cibendung, Kemantren Bantarsari, Kemantren Losari Upstream, Downstream Losari Kemantren, Kemantren Kubangjero, and Kemantren Rungkang. The purpose of this research is Become a reference from evaluation of performance of the irrigation area in irrigation area Pemali by analyzing the physical condition of building Although duct in the irrigation area of the Regional Irrigation Pemali, analyzing of human resource in the irrigation area of the Regional Irrigation Pemali, analyzing of rain Hydrology in the irrigation area of the Regional Irrigation Pemali, analyzing of income from weir Cibendong, analyzing of the patterns plants in the irrigation area of the Regional Irrigation Pemali, and analyzing planning plant and the realization of planting in the irrigation area of the Regional Irrigation Pemali. The method of this research is qualitative method, in the which the fission of the problem is explained that the subject or the object of research based on the facts roomates used during doing the research in the performance of irrigation system and try to make a good relation in deep from the aspects particularly subject. Based on the build irrigation condition in this area is classified as satisfactory with percentage of damage Reached 11.30%. Meanwhile, the duct condition in this irrigation area irrigation area is good Pemali classified with percentage of damage Reached 8.21%. The condition of the organizer in DI Jangkelok available irrigation area Pemali only 51 people, while in needed is 67 people with less percentage Reached 17.94% so that service toward the duct condition is less completed and have the impact to net condition wake or less roomates always damaged, this situation should be increased.From the results of the analysis of the ratio of demand with available discharge effective discharge rainfall added Irrigation Area in Jengkelok, Cibendung Weir fulfilled, but many unused discharge it is Necessary to modify the cropping pattern in order to maximize the potential of available discharge. The planting realization in 7 years ago in the irrigation area Irrigation Area Jangkelok Pemali it is less from the planning plant, but in the period of 2011/2012 Occurs Increased 7.34% and the realization of planting intensity is average 243.77% while the average of planning plan is 268.91% Tus in the lower plant productivity in this case since it can not be done to planting in this wide area.Keyword: Irrigation, Performance Analysis, Regional Irrigation